Influencing factor on the effectiveness of thermal comfort in the mosque / Suhaiza binti Sairi and Nazhatulzalkis binti Jamaludin - Sairi, Suhaiza; Jamaludin, Nazhatulzalkis (2019)
In hot-humid climate especially in the Malaysian situations, many mosques should be provided with acceptable level of thermal comfort in order to focus for worship. They are partially or fully occupied five times a day and the maximum occupancy is expected to occur on Friday prayers. As buildings with intermittent occupancy may not perform the same thermally as typical commercial and residential. This paper presents the results of satisfaction user during prayers in mosque order to assess thermal comfort conditions. The purpose of this study is to investigate the influence factors on the effectiveness of thermal comfort in the mosque. Have 2 mosque was selected as a test building and thermal condition were monitored during Friday prayers. Air temperature, relative humidity and air velocity were collected as a data and a questionnaire were calculated and evaluated using ASHREA 55-2010 standard and Malaysian standard 1525. A comparison is provided to highlight the difference between the calculated and perceived satisfaction of occupants.